The risk factors for early conversion to total knee arthroplasty after high tibial osteotomy. Issue 7 (19th May 2021) - Li, Hong-bo; Nie, Si; Lan, Min; Tang, Zhi-ming; Liao, Xin-gen
Abstract: The primary aim was to identify potential risk factors for early conversion to total knee arthroplasty (TKA) in patients with high tibial osteotomy (HTO) surgery. A retrospective study was conducted and 240 patients received HTO surgery between January 2008 and January 2014 were included in this study. The associations between different clinical factors and HTO survivorship were analyzed. A logistic regression analysis was performed to detect independent risk factors for HTO survivorship. The cut-off value, sensitivity and specificity of these independent factors were calculated by receiver operating characteristic (ROC) curve. In this study, thirty-five (14.6%) patients were early conversion to TKA within a 5-year follow-up. These results indicated that age, body mass index (BMI), preoperative Kellgren-Lawrence (K-L) grade and preoperative visual analogue scale (VAS) score were potential risk factors for HTO survivorship. The cut-off values of those factors were 60 years, 25.35 kg/m 2, 2 and 5, respectively. The combination of age, BMI, preoperative K-L grade and preoperative VAS score has the highest predictive value for HTO survivorship (AUC = 0.896, P < 0.001). Based on the present study, the five-year HTO survivorship for the treatment of medial compartment osteoarthritis of the knee was approximately 85.4%. We identified age >60 years, BMI >25.35 kg/m 2, preoperative K-L grade >2 and preoperative VAS score >5 as independent risk factors for early conversion to TKA in patients with HTO surgery, and those factors combined had the highest predictive value for predicting early conversion to TKA.